PENGARUH AROMATERAPI LAVENDER TERHADAP KUALITAS TIDUR IBU HAMIL TRIMESTER III DI TPMB S KOTA DEPOK TAHUN 2022 - Rusdi, Annisa (Journal of Midwifery Tiara Bunda, 2022)
Background: Difficulty Sleep is the condition in which a person is difficult to start or maintain sleep, almost all pregnant women experience difficulty to fulfill need get enough sleep. Third trimester mothers often experience various complaints, one of them that is disturbance or difficulty sleep. Lavender aromatherapy is one of them overcome quality lack of sleep. Purpose: The aim of this research is to find out influence of aroma lavender therapy against quality sleep of pregnant women in the third trimester at TPMB S city Depok. Metods: This type of research doubles Quantitative method with research design using quasi- experiment, in this study with a population of 32 respondents and a sample of 16 respondents. This res earch uses purposive sampling. Results: Then the data was analyzed using the Wilcoxon test to see the influence of aroma therapy to quality sleep of pregnant women in third trimester. Conclusion: The independent t-test statistical test obtained p value = 0.001 (p value < 0.05). then H0 is rejected and Ha is accepted. This shows that there is influence giving lavender aromatherapy against quality sleep of pregnant women in the third trimester